Radiographic Investigation of the Antegonial Angle, Antegonial Depth, Gonial Angle, and the Ramus Height to Estimate the Gender and Growth Patterns in Orthodontic Patients - Mahamad Irfanulla Khan; Tarika Gopal; S M Laxmikanth; Mathurampoyikayil Anju Varughese (Wolters Kluwer Medknow Publications, 2024)
Background: The antegonial angle (AGA), antegonial depth (AGD), gonial angle (GA), and ramus height (RH) of the mandible progress with age, gender, and dental condition. Aim: The aim of the study was to investigate the AGA, AGD, GA, and RH to assess the gender and growth patterns in orthodontic patients. Materials and Methods: Pre-treatment orthopantomograms and lateral cephalograms of 500 orthodontic patients with an age range of 13-30 years (mean ± SD: 19.63 ± 4.19) were selected. Based on the sagittal and vertical cephalometric measurements, they were divided into six groups. The AGA, AGD, GA, and RH were measured. The data were analyzed using the student's t-test and one-way ANOVA statistical tests. Results: The RH was short with an increased AGA, AGD, and GA in vertical growth patterns. In the class II group, the AGA, AGD, GA, and RH were found statistically significant. The females showed a higher AGA and GA, whereas the males had an increased RH and AGD. Conclusion: Class II skeletal pattern exhibited an increased AGA and AGD, while those with a class III skeletal pattern displayed an increased GA and RH. Gender differences showed that females exhibited a higher AGA and GA, whereas males had an increased RH and AGD.